SECONDARY DYSMENORRHOEA - Afridi, Bilqis (Journal of Ayub Medical College Abbottabad, 1989)
Abstract: Dysmenorrhoes is one of the major gynecological symptoms. 100 patients with secondary Dysmenorrhoea were analysed. Fibroid uterus, Endometriosis and pelvic inflammatory disease were the main pathological factors. Infertility, Menorrhagia, Abdominal pain were other common complaints in these patients. Retroversion of uterus was also a common associated finding in these patients.